Odpowiedzi

Najlepsza Odpowiedź!
2009-11-29T20:41:34+01:00
A).
2x + 5y = 7
3x - 5y = 3

5x = 10 /:5
x = 2

x = 2
2x + 5y = 7

x = 2
5y = 3 / :5

x = 2
y = 3/5


b)
x + 2y = 9
-x - 3y = 16

5y = 25 / :5
y = 5

y = 5
x + 2y = 9

y = 5
x = -1
2009-11-29T20:48:07+01:00
A)2x+5y=7
3x-5y=3
2x+5y+3x-5y=10
5x=10/5
x=2
2*2+5y=7
4+5y=7
5y=3/5
y=3/5

b)x+2y=9
-x-3y=16

x+2y-x-3y=9+16
-y=25/(-1)
y=-25

x+2*(-25)=9
x-50=9
x=9+50
x=59

x=59
y=-25
2009-11-29T21:02:04+01:00
A)2x + 5y = 7 |*(-3)
3x - 5y = 3 |*2

-6x-15y=-21
6x-10y=6

-25y=-15 |:(-25)
y=0,6

2x+5*0,6=3
2x+3=3|-3
2x=0|:2
x=0

x=0
y=0,6

b)x + 2y = 9
-x - 3y = 16

-y=25|:(-1)
y=-25

x+2*(-25)=9
x-50=9|+50
x=59

y=-25
x=59